Pengaruh Toksisitas minyak Azadirachta indica, Ricinus communis, dan campurannya: Pengaruhnya terhadap indeks nutrisi larva dan oviposisi imago Spodoptera frugiperda (J. E. Smith) pada tanaman jagung - Retno Wulansari; Yusup Hidayat; Danar Dono (Jurnal Entomologi Indonesia, 2022)
Spodoptera frugiperda (J. E. Smith) is an invasive pest that causes a high economic impact on maize. Alternative control that is relatively safe to non-target organisms that can be combined with other control strategies is botanical insecticides. This study aimed to evaluate the effect of Azadirachta indica (Meliaceae), Ricinus communis (Euphorbiaceae) oils, and their mixtures on mortality and nutritional indices and oviposition of S. frugiperda. The testing of toxicity and nutritional indices was done using the feed dipping method, while oviposition testing was conducted by spraying on treated plants. The relationship between concentration and mortality of tested insects was analyzed using probit analysis, while other data using analysis of variance. The results showed that A. indica, R. communis, and their mixtures were toxic to S. frugiperda larvae (II–VI) with LC50 values ​​of 0.039 (0.017–0.100)%, 0.144 (0.094–0.221)%, 0.034 (0.021–0.061)% respectively, and of LC95, 0.391 (0.134–16.671)%, 4.379 (1.986–15.516)%, 0.219 (0.104–1.251)%, respectively. The toxicity of the oil mixture increased 4.2 times to 20.0 times at LC50 and LC95, respectively. Oil treatments resulted in a decrease in the relative consumption rate, relative growth rate, food utilization efficiency, an increase in approximate digestibility of S. frugiperda. In addition, botanical oils act as antioviposition of S. frugiperda. However, A. indica, R. communis, and their mixtures were phytotoxic on maize. Therefore, the opportunity of a mixture of A. indica and R. communis oils to be used as an insecticide still needs to be evaluated or can be used on other plants that are more tolerant.